Co-occurrence of MGMT gene promoter methylation and amplification of EGFR in glioblastoma - Adamek, Dariusz; Zazula, Monika; Radwańska, Edyta; Grzywna, Ewelina; Sińczak-Kuta, Anna; Moskała, Marek (Contemporary Oncology/Współczesna Onkologia, 2011)
Introduction : The way to improve the efficiency of chemotherapy of malignant gliomas may be combined administration of alkylating agents and those targeted at epithelial growth factor receptor (EGFR). The patients eligible for such therapy should show hypermethylation of MGMT (O6-methylguanine-DNA-methyltransferase) promoter as well as amplification of EGFR. Aim of the study : Preliminary assessment of frequency of MGMT hypermethylation and amplification of EGFR co-occurrence in malignant gliomas in patients diagnosed and operated on in the Neurosurgery Department, JUMC in Cracow. Material and methods : 21 consecuti-ve cases of glioblastoma multiforme (W 65%, M 35%, age average 51 y). The methylation status of the MGMT promoter was determined by methylation-specific PCR (MS-PCR). Before MS-PCR, genomic DNA was treated with sodium bisulphite, purified, denatured, precipitated and eluted. EGFR amplification was investigated using the FISH method. Results : With regards to MGMT methylation status and the occurrence of EGFR amplification, four groups of tumours (patients) were established: I – hypermethylation and amplification (4/21, 19.04%); II – hypermethylation, no amplification (6/21, 28.6%); III – no hypermethylation with amplification (4/21, 19.04%); IV – no hypermethylation, no amplification (7/21, 33.3%). Conclusions : Theoretically almost one fifth (19%) of patients with glioblastoma multiforme, i.e. those featuring MGMT hypermethylation and EGFR amplification, could potentially benefit from bimodal chemotherapy with an alkylating agent and an EGFR blocker. Our results confirm other reports indicating that there are no relations between MGMT methylation and EGFR amplification. Financial support by Grant No. K/ZDS/ 001044 Jagiellonian Univ.